A fatal case of fulminant neuroleptic malignant syndrome: A case report. Issue 1 (23rd January 2023) - Komoriya, Hitomi; Nomura, Konoka; Shirata, Toshinori; Kobayashi, Tadahiro; Nakane, Masaki; Noto, Keisuke; Kobayashi, Ryota; Suzuki, Akihito
Abstract: Background: Neuroleptic malignant syndrome (NMS), a rare but potentially life‐threatening adverse reaction to treatment with antipsychotic drugs, is characterized by hyperthermia, muscle rigidity, impaired consciousness, and autonomic disturbances. Some reports have described rapidly progressing cases of NMS resulting in death within several days. This report describes a clinical course of fatal and fulminant NMS in a patient with schizoaffective disorder. Case Presentation: A 67‐year‐old man had long been in a stable condition under antipsychotic pharmacotherapy. At 3 days before admission to our hospital, he complained of diarrhea, fatigue, and reduced appetite. On admission to our hospital, he showed fever, mild muscle rigidity at the four extremities, elevated heart rate, hypertension, excessive diaphoresis, and decreased percutaneous oxygen saturation (SpO2 ). He was diagnosed as having NMS. Within 3 days after the onset of NMS, he displayed severe hyperthermia up to 41.4°C and severe autonomic disturbances, including elevated heart rate and hypertension. Despite treatments with dantrolene and bromocriptine, he went into shock and died on the fourth day after admission. Conclusion: The present case suggests that severe hyperthermia and severe autonomic disturbances at the early stage of the onset might be signs of fatal and fulminant NMS. It may be recommended that clinicians consider electro‐convulsive therapy when treating fulminant NMS with these symptoms.